Empowering NGOs? Long-term effects of ecological and institutional change on regional fisheries management organizations. (November 2020) - Dellmuth, Lisa M.; Petersson, Matilda T.; Dunn, Daniel C.; Boustany, André; Halpin, Patrick N.
Highlights: Scientist and expert participation in RFMOs tends to crowd out NGO participation. NGOs participate in greater numbers in RFMOs with relatively large budgets. In RFMOs with more democratic memberships, we find more NGO participation. Target fish stock health is not found to shape NGO participation. NGOs participation does not seem to depend on the economic value of target stocks. Abstract: The participation of environmental non-governmental organizations (ENGOs) in regional fisheries management organizations has inspired optimism among many observers and researchers about increasing the effectiveness of these regional organizations in managing highly migratory and straddling fish stocks sustainably. Others claim that the attendance of ENGOs in meetings of regional fisheries management organizations as accredited observers or as part of member state or cooperating non-member state delegations, could make decision-making complex, long, and inefficient. More generally, NGO participation has attracted broad scholarly interest in the study of interest groups and transnational advocacy in political science. Yet, we know little about the determinants of ENGO participation in meetings of regional fisheries management organizations in the first place. To fill this gap, this article develops a theoretical framework conceptualizing ENGO participation and developing expectations about how ecological and institutional change shapes ENGO participation. The framework deals with structural determinants of ENGO participation, as existing literature primarily has been preoccupied with the study of actor-specific explanations of specific NGOs' impact in specific political processes. By contrast, we examine how ecological change – such as target fish stock health and biomass status – and institutional change – such as financial resources, membership composition of regional fisheries management organizations and participation by other non-state actors, such as experts and fishing industry representatives – shape ENGO participation. We empirically explore this framework in the context of seven regional fisheries management organizations. A dataset comprising yearly fish stock-level data on participation, institutional, and ecological factors, for 1980–2014, was compiled for our quantitative inquiry into the determinants of ENGO participation. We find robust evidence that institutional change shapes ENGO participation, but not ecological factors related to target fish stock health. We discuss our findings against the backdrop of ongoing debates about NGOs in political science, and spell out broader implications for future research on NGOs in regional fisheries management organizations.